Педагогічні умови національно-патріотичного виховання дітей передшкільного віку засобами української народної іграшки - Козоріз, Дмитро Володимирович (My University, 2024)
Наукова робота присвячена аналізу проблеми національно-патріотичного виховання дошкільників. Проаналізовано специфіку передшкільного віку щодо формування засад патріотизму у дітей. Розкрито патріотично-виховний потенціал української народної іграшки. Дослідження ґрунтується на педагогічних, психологічних, культурологічних, історичних аспектах використання народної іграшки. З метою проведення констатувального етапу експерименту розроблено необхідний діагностичний інструментарій. Виявлено рівні патріотичної вихованості дітей передшкільного віку засобами народної іграшки. Проаналізовано чинники впливу на ефективність процесу національно-патріотичного виховання дітей з урахуванням впливу народної іграшки. На основі зробленого експерименту було розроблено педагогічні умови національно-патріотичного виховання дітей передшкільного віку засобами народної іграшки. Укладено методичні матеріали до кожної з означених умов, що на думку автора, сприяє ефективності роботи вихователя ЗДО відносно національно-патріотичного виховання дітей передшкільного віку засобами народної іграшки.
Pedagogical conditions of national-patriotic education of preschool children by means of Ukrainian folk toys
The scientific work is devoted to the analysis of the problem of national-patriotic education of preschoolers. The specificity of preschool age in terms of the formation of the foundations of patriotism in children is analyzed. The patriotic and educational potential of Ukrainian folk toys is revealed. The study is based on the pedagogical, psychological, cultural, and historical aspects of the use of folk toys. In order to conduct the ascertaining stage of the experiment, the necessary diagnostic tools were developed. The levels of patriotic education of preschool children by means of folk toys were identified. Factors influencing the effectiveness of the process of national-patriotic education of children, taking into account the influence of folk toys, were analyzed. Based on the experiment, pedagogical conditions for national-patriotic education of preschool children by means of folk toys were developed. Methodological materials for each of the specified conditions are compiled, which, in the author's opinion, contributes to the effectiveness of the work of the preschool teacher in relation to the national-patriotic education of preschool children using folk toys. Keywords: patriotism, patriotic education, patriotic feelings, national-patriotic education, preschool age, national culture, folk toy, Ukrainian folk toy
Keywords: патріотизм; патріотичне виховання; національно-патріотичне виховання; патріотичне виховання дошкільників; українська народна іграшка; виховання патріотичних почуттів